- BRIEFING BOOK - TOBACCO TAXES AND HEALTH CARE FINANCING (Tufts Archival Research Center, 2007)
Briefing book on cigarette taxes and health care financing. Includes information relating to various demographic groups and organizations. Discusses competing proposals, the regressive nature of cigarette taxes, and economic effects for each state. Reprints the congressional testimony of allies.